Natural Heat-Related Deaths in Florida: 2010-2020 - Serap Gorucu; Clyde Fraisse; Ziwen Yu (EDIS)
This publication discusses heat-related deaths in Florida from 2010 to 2020 and presents safety recommendations as well as useful resources to prevent heat-related illnesses. Written by Serap Gorucu, Clyde Fraisse, and Ziwen Yu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, May 2021.